Recycled materials detection / Hanisah Mohd Ali - Mohd Ali, Hanisah (2021)
Recycling is a process that uses methods of collecting, processing and reusing materials that are considered no longer valuable. The importance of a cycle management practice good recycling is applied to reduce congestion at waste landfills. Malaysia faces rapidly increasing solid waste, especially household waste. There are some problems that make this research happen is lack of technology on solid waste management and recycling and less attention of awareness in recycling. For this research focus at solid waste which is research domain and for research area is focus at image processing. This research is about to improve the technology in solid waste management. With these research area and research domain, this project trying to make a new technology based on image processing. Besides that, this research trying to figure out the best methodology that can be use in this project to complete and the processes can follow the plan smoothly. There is sequence of research approach which is theoretical study, knowledge acquisition, data collection, design and develop prototype and implementation. This research also will discuss about project design, project development and project implementation after develop the system. This system is developed to make it simple and easy to use. This research will explain about the conclusion of development for this project either this project is success to reach the project objective or not.